2020
DOI: 10.3389/fneur.2019.01405
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Posterior Reversible Leukoencephalopathy Syndrome Triggered by FLOT Chemotherapy

Abstract: Posterior reversible encephalopathy syndrome (PRES) is a potentially severe disorder of the autoregulation of cerebral perfusion. The major clinical manifestations are headache, seizures, altered mental status, and visual loss. The typical radiological finding is vasogenic edema predominating in the white matter of occipital and parietal lobes. PRES is increasingly recognized as a clinico-radiological entity owing to improvements and fast availability of brain imaging, especially magnetic resonance imaging (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Numerous studies have demonstrated that cytotoxic agents can induce endothelial dysfunction, leading to the production of vasoactive substances, vascular leakage, and the development of cerebral edema. 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have demonstrated that cytotoxic agents can induce endothelial dysfunction, leading to the production of vasoactive substances, vascular leakage, and the development of cerebral edema. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 6 In 2015, three clinico-radiological criteria were suggested for the diagnosis of PRES: acute neurological signs, vasogenic edema on neuroimaging and reversibility of clinical and/or radiological signs. 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of PRES is related to endothelial cell injury caused by the application of cytotoxic drugs such as cyclophosphamide and doxorubicin, and systemic chemotherapy has been reported in the past [ 15 ]. Besides doxorubicin, many previous literatures [ 16 , 17 ] have reported that chemotherapy with 5-fluorouracil or/and oxaliplatin could cause PRES. Although the cases we report were treated with 5-fluorouracil or oxaliplatin, and epirubicin locally to the arterial system, the two patients did not receive chemotherapy for eight weeks before operation, but the specific changes in clinical symptoms and imaging findings were potentially strongly correlated with the time of local application of chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%